2016
DOI: 10.21147/j.issn.1000-9604.2016.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for locally advanced cervical cancer

Abstract: Neoadjuvant chemotherapy followed by surgery (NCS) has not been fully evaluated clinically. Currently, the main regimen of neoadjuvant chemotherapy (NAC) used in NCS includes cisplatin. The antitumor effects of NAC reduce lymph node metastasis and the tumor diameter in patients prior to surgery, and this can reduce the number of high risk patients who require postoperative radiation therapy. Many randomized controlled trials (RCTs) have examined the long-term prognosis of NCS compared to primary surgery, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Colo do útero Neoadjuvante, Adjuvante, terapia definitiva, terapia combinada, tratamento metastático, segunda linha. ROSE et al, 1999;GREEN et al, 2001;BENEDETTI-PANICI et al, 2002;RAHAMAN et al, 2009;ASANO;DAWOOD;INSTONE;KEHOE, 2013;TODO;WATARI, 2016;IWATA et al, 2016 Câncer de ovário Neoadjuvante, Adjuvante, terapia em estágio avançado, primeira linha, terapia combinada LUND et al, 1990;PICCART et al, 2000;HÖGBERG;GLIMELIUS;NYGREN, 2001;MARKMAN et al, 2001;OZOLS et al, 2003;ARMSTRONG et al, 2006;HELM;STATE, 2009;BERGAMINI et al, 2017 Câncer endometrial Adjuvante, terapia combinada DUNTON et al, 1991;FUJIMURA et al, 2000;AAPRO et al, 2003;RANDALL et al, 2006;SUSUMU et al, 2008;GALAAL et al, 2014; Câncer de vulva Neoadjuvante, adjuvante, terapia combinada, terapia metastática SHIMIZU et al, 1990;BEREK et al, 1991;BENEDETTI-PANICI et al, 1993;BELLATI et al, 2005;GEISLER;MANHAN;BULLER, 2006;RICHARD et al, 2008;CORMIO et al, 2009;ARAGONA et al, 2012; Câncer de vagina Neoadjuvante, Adjuvante, terapia combinada, terapia metastática ROBERT et al, 1991;...…”
Section: Cisplatinaunclassified
“…Colo do útero Neoadjuvante, Adjuvante, terapia definitiva, terapia combinada, tratamento metastático, segunda linha. ROSE et al, 1999;GREEN et al, 2001;BENEDETTI-PANICI et al, 2002;RAHAMAN et al, 2009;ASANO;DAWOOD;INSTONE;KEHOE, 2013;TODO;WATARI, 2016;IWATA et al, 2016 Câncer de ovário Neoadjuvante, Adjuvante, terapia em estágio avançado, primeira linha, terapia combinada LUND et al, 1990;PICCART et al, 2000;HÖGBERG;GLIMELIUS;NYGREN, 2001;MARKMAN et al, 2001;OZOLS et al, 2003;ARMSTRONG et al, 2006;HELM;STATE, 2009;BERGAMINI et al, 2017 Câncer endometrial Adjuvante, terapia combinada DUNTON et al, 1991;FUJIMURA et al, 2000;AAPRO et al, 2003;RANDALL et al, 2006;SUSUMU et al, 2008;GALAAL et al, 2014; Câncer de vulva Neoadjuvante, adjuvante, terapia combinada, terapia metastática SHIMIZU et al, 1990;BEREK et al, 1991;BENEDETTI-PANICI et al, 1993;BELLATI et al, 2005;GEISLER;MANHAN;BULLER, 2006;RICHARD et al, 2008;CORMIO et al, 2009;ARAGONA et al, 2012; Câncer de vagina Neoadjuvante, Adjuvante, terapia combinada, terapia metastática ROBERT et al, 1991;...…”
Section: Cisplatinaunclassified
“…Several other agents and drug combinations, including the taxanes, have been investigated as radiation sensitisers in CC. The most recent review of 13 different chemotherapy regimens concomitant to RT in the treatment of LACC indicated that CCRT with cisplatin/docetaxel might be the most effective (39). However, weekly cisplatin remains the least toxic among all chemotherapy regimens in combination with RT.…”
Section: Cytotoxic Agents Used In Combination With Rtmentioning
confidence: 99%
“…In China, the incidence of cervical cancer has increased rapidly over the past 20 years ( 3 ). Surgery, radiotherapy and chemotherapy are currently the main treatment methods for cervical cancer ( 4 ). Although advances in these therapies have prolonged patient survival, the limitations of effective regimens are the resistance of tumor cells and their severe side effects ( 5 ).…”
Section: Introductionmentioning
confidence: 99%